CARACTERIZAÇÃO DO STAPHYLOCOCCUS COAGULASE NEGATIVO ISOLADOS DE QUARTOS MAMÁRIOS DE VACAS COM MASTITE SUBCLÍNICA - Ribeiro, Marlice Teixeira; Sá, Wanderlei Ferreira De; Melchíades, Leda Aroni; Veiga, Vânia Maria De Oliviera; Dutra, Iveraldo Santos [UNESP] (Universidade Federal de Santa Maria, 1994)
SUMMARY The present work was carried out in the region of Zona da Mata-MG, Brazil, during three months. Sixteen crossbreed cows and nineteen Holstein-Friesian cows from four herds were used. The work aimed to characterize coagulase negative Staphylococcus spp. from those animals. The mammary quarters which reacted positive with the California Mastitis test on four consecutive weeks were sampled. A total of 166 strains were isolated. The identified species and the percentage of isolation were as follows: S. epidermidis (71.55%), S. hyicus subsp. chromogenes (6.03%), S. simulans (6.03%), S. warneri (4.31%), S. hominis (3.45%), S. cohnii (3.45%), S. sciuri (3.45%) and S. haemolyticus (1.73%).

RESUMO O presente trabalho foi desenvolvido na Zona da Mata - MG, durante três meses. De quatro rebanhos utilizados, trabalhou-se com 16 animais mestiços e 19 holandeses. O objetivo foi caracterizar Staphylococcus coagulase negativos, isolados de quartos mamários de vacas, que inicialmente reagiam à prova do Califórnia Mastitis Test (CMT), em quatro testes consecutivos, a intervalo de uma semana. A caracterização das 116 amostras encontradas, correspondentes a Staphylococcus coagulase negativo, foram: S. epidermidis (71,55%), S. hyicus subsp. chromogenes (6,03%), S. simulans (6,03%), S. warneri (4,31%), S. hominis (3,45%), S. cohnii (3,45%), S. sciuri (3,45%) e S. haemolyticus (1,73%).
CHARACTERIZATION OF COAGULASE NEGATIVE STAPHYLOCOCCUS ISOLATED FROM THE MAMARY QUARTERS OF THE COWS WITH SUBCLINICAL MASTITIS
Keywords: mastite; Staphyiococcus coagula-se negativo; mastite subclínica; mastitis; coagulase negative Staphylococcus; subclinical mastitis